The Effect of Capital Structure, Firm Size, Firm Growth, And Profitability on Firm Value (Empire Study on Mining Sector Companies Listed on The Indonesia Stock Exchange 2015-2020) - Tasya Novitasari; Sunarto Sunarto (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
The purpose of this study was to determine the effect of capital structure, firm size, firm growth, and profitability on firm value in mining sector companies listed on the Indonesia Stock Exchange for the 2015-2020 period. The capital market is a means for making investments that allow investors to place their funds in an asset according to the risk they are willing to bear with the expected level of profit. In this research, the research method used is the descriptive quantitative method. The number of samples in this study is 116 data from companies in the mining sector on the IDX. Determination of the sample using the purposive sampling technique. The data collection technique uses the documentation method by collecting records and documentation that leads to more accuracy. In proving and analyzing this, the classical assumption test, multiple linear regression test and f test (simultaneous), and t-test (partial) are used. The test results show that the variables of capital structure, firm size, firm growth, and profitability simultaneously affect firm value. The results of the partial test show that the capital structure (X1) has a sig value of 0.000 which means ≤ 0.05 so that it affects the firm value. Company size (X2) has a sig value of 0.695, which means ≥ 0.05 so it has no effect on firm value. The firm growth (X3) has a sig value of 0.189, which means ≥ 0.05 so it has no effect on firm value. Likewise with the profitability variable (X4) has a sig value of 0.950 which means ≥ 0.05 so it does not affect firm value.